Does Living in Human-Altered Environments Affect Life-History and Personality of Wild Mice? - Küçüktaş, Fulya Mina; Guenther, Anja (Frontiers in Ecology and Evolution, 2022)
In urban habitats, animals are faced with different and often challenging environmental conditions compared to their native habitats. Behavior is the fastest response to environmental change and therefore a very important component to adjust to human-altered environments. Behaviors such as novelty responses and innovativeness which allow animals to cope with novel stimuli are often altered in urban populations. The mechanisms producing such adaptations are currently not well understood. In this study, we investigate whether urban living has an impact on the microevolution of mouse behavioral and life-history traits including boldness, stress-coping, growth, longevity, and emphasis on reproduction. We hypothesized that animals living together with humans for longer show increased novelty-seeking and boldness characteristics at the species and subspecies level. We, therefore, compared behavior and life history characteristics among Mus musculus, a commensal rodent, Mus spicilegus as a synanthropic but not commensal, and Apodemus uralensis as a strictly rural species. In addition, we compared three subspecies of Mus musculus (in total six populations) that differ in the time living together with humans. Behavioral and life history differences are stronger between populations even of the same subspecies rather than showing a structural trend with the time animals have spent with humans. In addition, species differ in behavior and life history, albeit not in a pattern that suggests an evolutionary adaptation to living in human-altered habitats. We, therefore, suggest that behavioral adaptations of wild mice are geared towards environmental differences such as geographic origin or habitat specifics but not necessarily directly evolve by living together with humans.